Bortezomib‐Cyclophosphamide‐Dexamethasone (VCD) versus Bortezomib‐Thalidomide‐Dexamethasone (VTD) ‐based regimens as induction therapies in newly diagnosed transplant eligible patients with multiple myeloma: a meta‐analysis. (26th May 2014) - Leiba, Merav; Kedmi, Meirav; Duek, Adrian; Freidman, Tzachi; Weiss, Mia; Leiba, Ronit; Nagler, Arnon; Avigdor, Abraham
Summary Three‐drug induction regimens have become the standard of care in newly diagnosed transplant‐eligible multiple myeloma patients. Two frequently used protocols are bortezomib, cyclophosphamide and dexamethasone (VCD) and bortezomib, thalidomide and dexamethasone (VTD). Comparisons between the two are lacking. The present study aimed to identify the differences in response rate and toxicity between the two regimens. Databases were searched using the terms 'VTD' or 'VCD' and 'induction regimens for newly diagnosed multiple myeloma'. Prospective trials evaluating initial response in transplant eligible patients were included. The main outcome measures were response rates and adverse events. Eight clinical trials were eligible for analysis. Overall 672 patients were treated with either VCD (n = 157) or VTD (n = 515) as induction therapy. Patients treated with VTD presented with a significantly higher complete/near complete response (34% vs. 6%, P = 0·002) as well as a higher very good partial response rate or better, following induction therapy (62% vs. 27%, P < 0·0001). Although grade 3–4 neurotoxicity was more frequent during VTD therapy (11% vs. 6%, P = 0·057), a higher incidence of overall grade 3–4 adverse events was found in the VCD‐treated patients (74% vs. 51%, P < 0·001). VTD induction therapy may be superior in achieving deeper response rate following induction therapy, and is better tolerated.